2018
DOI: 10.1088/1748-9326/aac4d1
|View full text |Cite
|
Sign up to set email alerts
|

Tradeoffs in the quest for climate smart agricultural intensification in Mato Grosso, Brazil

Abstract: Low productivity cattle ranching, with its linkages to rural poverty, deforestation and greenhouse gas (GHG) emissions, remains one of the largest sustainability challenges in Brazil and has impacts worldwide. There is a nearly universal call to intensify extensive beef cattle production systems to spare land for crop production and nature and to meet Brazil's Intended Nationally Determined Contribution to reducing global climate change. However, different interventions aimed at the intensification of livestoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 48 publications
0
33
0
3
Order By: Relevance
“…The growth and development of crops and forages are predicted daily based on the availability of water and nutrients in the soil, ambient temperature and solar radiation absorbed by the system [ 27 ]. Grazing animals are kept outdoors throughout the year, but pasture growth may not be available for some periods of the year, so feeding strategy is defined by the groups of animals present in the pasture and by the amount of time they have access to the pasture.…”
Section: Methodsmentioning
confidence: 99%
“…The growth and development of crops and forages are predicted daily based on the availability of water and nutrients in the soil, ambient temperature and solar radiation absorbed by the system [ 27 ]. Grazing animals are kept outdoors throughout the year, but pasture growth may not be available for some periods of the year, so feeding strategy is defined by the groups of animals present in the pasture and by the amount of time they have access to the pasture.…”
Section: Methodsmentioning
confidence: 99%
“…Within this context, Brazilian agriculture has global relevance due to the large proportion of the world's tropical forests, water and biodiversity (Gil et al, ). Agricultural areas bordering environmentally sensitive regions are also responsible for the greatest beef (ABIEC, ) and grain (CONAB, ) production in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…The financial accounting approach used here, which is based on observed outcomes, is also a useful complement to process models, which predict outcomes based on inputs (e.g. Gil et al ., 2018 for the same region).…”
Section: Methodsmentioning
confidence: 90%
“…Prior studies in Brazil, especially in the Cerrado, have also shown that iCL systems can increase production efficiency since they contribute to: (i) improvements in soil quality; (ii) water conservation; (iii) an increase of animal performance; and (iv) a reduction in GHGs per unit of food produced (Kluthcouski et al ., 2003; Macedo, 2009; Vilela et al ., 2011; Salton et al ., 2014). What is less understood is how economically viable these productions systems are in the Legal Amazon region of Brazil, particularly in light of their potentially high initial investment costs (Gil et al ., 2018) and (Appendix 1). This lack of generalized information about the economic performance of iCL in the country's largest cattle and crop production region may help explain its low adoption rates, despite fairly high levels of government support (Martha JĂșnior et al ., 2011; Vilela et al ., 2011; De Oliveira et al ., 2013; Salton et al ., 2014; Reis et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%